Yonsei criteria: a clinical reflection of stage I left-sided pancreatic cancer - Chong, Jae Uk (Oncotarget, 2017)
In this study, we examined associations between pancreatic cancer that met the Yonsei criteria (YC) and classifications from the 8th edition of the American Joint Committee on Cancer (AJCC) staging system. Clinicopathological and survival data were collected from132 patients who underwent distal pancreatectomy for left-sided pancreatic ductal adenocarcinoma between January 2000 and December 2015, and the utility of the YC for selecting treatment and predicting survival was evaluated using the 8th AJCC staging manual. Of the 102 patients who ultimately qualified for the study, 45 patients were reclassified as stage I based on the 8th AJCC cancer staging system. Disease-free survival and disease-specific survival periods were longer in stage I patients who met the YC than in those who did not. Clinicopathological characteristics did not differ between stage I patients who did and did not meet the YC. These results suggest that meeting the YC criteria may be a clinical indicator that left-sided pancreatic cancer patients who are candidates for resection have early-stage disease according to the 8th edition of the AJCC staging manual.